Efektivitas Mahasiswa Gizi dalam Pembelajaran Bahasa Inggris Melalui Literasi Digital di Poltekkes Kemenkes Riau - Falinda Oktariani (Journal Khafi : Journal Of Islamic Studies, 2023)
This study adopts a qualitative approach to explore the effectiveness of using digital literacy in learning English for students of the Nutrition study program at the Riau Ministry of Health Polytechnic. The purpose of this study is to gain an in-depth understanding of students' experiences in integrating digital literacy into learning English and its impact on their English proficiency and learning experiences. This research method uses a case study approach with data collection through in-depth interviews and document analysis. The research participants consisted of students from the Nutrition study program who had taken English lessons with digital literacy. Data from interviews and document analysis were analyzed using a thematic analysis approach to identify patterns, themes, and the meanings that emerge from student experiences. These findings provide a richer perspective on how digital literacy can be applied effectively in the context of health education. The implications of this research also contribute to the development of learning strategies that are more adaptive in dealing with the digital era and globalization.